Non-coding RNAs – A primer for the laboratory scientist. Issue 4 (2nd October 2019) - Waller, P; Blann, AD
ABSTRACT: Advances in molecular genetics have identified several species of RNA that fail to translate – hence the non-coding RNAs. The two major groups within this class of nucleic acids are microRNAs (miRNA) and long non-coding RNAs (lncRNA). There is growing body of evidence supporting the view that these molecules have regulatory effect on both DNA and RNA. The objective of this brief review is to explain the molecular genetic of these molecules, to summarize their potential as mediators of disease, and to highlight their value as diagnostic markers and as tools in disease management.